2016
DOI: 10.1016/j.tvjl.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of whole body protein synthesis and plasma amino acid concentrations in yearling horses fed graded amounts of lysine

Abstract: Lysine has been reported as the first limiting amino acid in typical equine diets. Indicator amino acid oxidation (IAAO) has become the standard method for determining amino acid requirements in other species, but prior to this study, it has not been used to determine equine requirements. The aim of this study was to evaluate whole body protein synthesis and plasma and muscle amino acid concentrations in response to graded levels of lysine intake in yearling horses. Six Thoroughbred colts (358 ± 5 kg) were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
11
1
Order By: Relevance
“…An increase in protein synthesis was observed at 204 μM as well as at 408 μM leucine but not at 102 μM leucine (P < 0.02; Figure 2). Average plasma leucine concentrations in the horse range between 80 and 160 μM (Westermann et al, 2011;Peters et al, 2013;Mastellar et al, 2016) just below the concentration at which statistical differences were observed in this study. No effect was observed between 25 and 102 μM leucine, suggesting that in these experiments those concentrations did not reach the threshold needed to detect an increase in 3 H-Phe incorporation into equine satellite cell proteins.…”
Section: Protein Synthesis Assaycontrasting
confidence: 59%
“…An increase in protein synthesis was observed at 204 μM as well as at 408 μM leucine but not at 102 μM leucine (P < 0.02; Figure 2). Average plasma leucine concentrations in the horse range between 80 and 160 μM (Westermann et al, 2011;Peters et al, 2013;Mastellar et al, 2016) just below the concentration at which statistical differences were observed in this study. No effect was observed between 25 and 102 μM leucine, suggesting that in these experiments those concentrations did not reach the threshold needed to detect an increase in 3 H-Phe incorporation into equine satellite cell proteins.…”
Section: Protein Synthesis Assaycontrasting
confidence: 59%
“…In previous studies, skeletal muscle mass accumulation was attributed to the relative efficiency between muscle protein synthesis and degradation [3,4,33]. Nevertheless, our GO enrichment analysis results obtained from the iTRAQ analysis showed that there were great changes in skeletal muscle structure and muscle cell function.…”
Section: Discussionmentioning
confidence: 62%
“…Lysine (Lys) is the first limiting essential amino acid for mammals consuming a predominantly cereal-based diet [1,2]. The important role of Lys in promoting skeletal muscle growth has already been demonstrated in animal husbandry, and this effect was attributed to increased protein synthesis [3,4]. Moreover, the functions of Lys in preventing human illnesses, such as osteoporosis and maldevelopment, have been intensively studied to protect human health [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Lysine has been suggested as the first limiting amino acid in growing horses (Graham et al, 1994;Ott, Asquith, & Feaster, 1981;Potter & Huchton, 1975). Moreover, a previous study reported that histidine might be a candidate for a limiting amino acid in equine diet, which mainly consisted of soy hull and corn (Mastellar, Coleman, & Urschel, 2016;Tanner et al, 2014), and the experimental diets used in the present study were also composed of large amounts of soy hull (38%, as-fed basis) and corn (16%, as-fed basis; Table 1). These previous findings support a possibility that one or more of the other amino acids may have been more limiting than threonine, resulting in a lack of responsiveness of phenylalanine oxidation to increasing levels of dietary threonine.…”
Section: Discussionmentioning
confidence: 92%